2021
DOI: 10.1002/ejsp.2796
|View full text |Cite
|
Sign up to set email alerts
|

Are COVID‐19 conspiracies a threat to public health? Psychological characteristics and health protective behaviours of believers

Abstract: We tested the link between COVID‐19 conspiracy theories and health protective behaviours in three studies: one at the onset of the pandemic in the United Kingdom (UK), a second just before the first national lockdown, and a third during that lockdown ( N = 302, 404 and 399). We focused on conspiracy theories that did not deny the existence of COVID‐19 and evaluated the extent to which they predicted a range of health protective behaviours, before and after controlling for psychological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 100 publications
(155 reference statements)
2
46
1
Order By: Relevance
“…Indeed, it is possible that an excess of fear and uncertainty, rather than lack of information, drives engagement in behaviors without an evidence base. This echoes a prior research finding that COVID-19 conspiracy theorists showed increased rates of protective behaviors, both those that were and those that were not recommended by governmental bodies [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, it is possible that an excess of fear and uncertainty, rather than lack of information, drives engagement in behaviors without an evidence base. This echoes a prior research finding that COVID-19 conspiracy theorists showed increased rates of protective behaviors, both those that were and those that were not recommended by governmental bodies [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…The stronger, more accessible, stable, and specific the attitude, the more likely that attitude is to lead to behaviors that are consistent with that attitude. We would, therefore, expect that when it comes to COVID vaccination, a similar trend would emerge, which has been observed in previous studies specific to the COVID vaccine (e.g., Juanchich et al, 2021, Wolff, 2021. That is, the conclusion that some individuals have pre-existing anti-vaccine attitudes that result in a bias against receiving the COVID vaccine is well-founded and one we expected to reproduce in the current study.…”
Section: Attitudes and Decision Makingsupporting
confidence: 83%
“…Although acceptance of pseudoscience beliefs or COVID conspiracies are often pointed to as strong primary differentiators among those who have chosen to vaccinate and those who have not (e.g., Juanchich et al, 2021;Jennings et al, 2021), our results indicate that both variables are, at most, distal predictors of vaccination decisions. Rather, acceptance of conspiracies and pseudoscience beliefs appear to be only a small component of vaccine hesitancy.…”
Section: Discussioncontrasting
confidence: 52%
“…Our results complement these findings and extend them also to the domain of more general actions of non-compliance with government regulations and violent protests. Although, not all studies found link between endorsement of conspiracy theories and lowered adherence to health protective behaviors (Imhoff and Lamberty, 2020;Juanchich et al, 2021), it largely depends on the what kinds of behaviors were examined. For example, people believing in conspiracy theories in Juanchich et al (2021) washed their hands as often as non-believers, but they were still less willing to install the contact-tracing app or get vaccinated, i.e., socially oriented behaviors.…”
Section: Discussionmentioning
confidence: 99%